Statistical Process Control for the Food Industry : A Guide for Practitioners and Managers - Lim, Sarina Abdul Halim, author; Antony, Jiju, author (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
Includes bibliographical references and index.